A joint decoding algorithm for multiple-example-based addition of words to a pronunciation lexicon - Bansal, D.; Nair, N.; Singh, R.; Raj, B. (2009 IEEE International Conference on Acoustics, Speech and Signal Processing, 2009)
We propose an algorithm that enables joint Viterbi decoding of multiple independent audio recordings of a word to derive its pronunciation. Experiments show that this method results in better pronunciation estimation and word recognition accuracy than that obtained either with a single example of the word or using conventional approaches to pronunciation estimation using multiple examples.